Healthcare-transition risk assessment for emerging adults with diabetes type 1 - Kaye, J.; Rapley, Pat; Babel, G.; Brown, S. (Scientific Research Publishing, Inc., 2013)
Aim: To identify potential risk indicators for emerging adults transitioning to adult health care. Background: Without maturity, independence, knowledge and motivation to manage their diabetes and successfully transition to adult healthcare, a proportion of emerging adults will struggle, leaving themselves vulnerable to diabetes-related complications. Methods: Fifty-three emerging adults (aged 17 - 19 years) recently transitioned from pediatric to adult healthcare were recruited. Data included demo-graphic, glycated haemoglobin, Body Mass Index, base-line and 12-month data from four psychosocial measures: Problem Areas in Diabetes, Diabetes Empowerment Scale, Hospital Anxiety and Depression Scale and dichotomous questions from the Eating Attitude Test. Missed appointments were obtained from hospital re-cords. Results: No significant differences in age, gender, BMI and individual survey scales between three appointment groups. Median HbA1c in the Sat-1 group was 7% (53 mmol/mol), compared with 8.6% (70 mmol/mol) and 8.5% (69 mmol/mol) respectively in the Sat-2 and Unsatisfactory groups. A ROC curve analysis and classification tree analysis identified optimal threshold values for the survey scales and their linear combinations. These values were used to make comparisons across two appointment and three HbA1c status groups. The unsatisfactory appointment group was characterised by statistically higher proportions of participants with (1) a low score for empowerment alone or in combination (less) with perceived problems and (2) statistically higher perceived problems and anxiety scores.Conclusions: Findings suggest that diabetes self-care confidence, less perception of diabetes as a problem, could be a useful indicator of future appointment attendance. Similarly, depression levels could be a useful predictor of better metabolic control following transition. Relevance to clinical practice: This study offers an innovative use of existing metrics to identify at-risk emerging adults in a busy clinic. Rather than the emphasis being solely on blood glucose control, it may be time to consider including psychosocial measures to identify at-risk individuals at the first appointment in adult healthcare.